Differential Growth Responses of Oryza sativa L. cv. KDML105 Seedling to IAA-Producing PGPR under Soil and Nutrient Solution Systems - Atnaseo, Chuthamat; Phakham, Wannausa (วารสารผลิตกรรมการเกษตร, 2026)
Plant growth promoting rhizobacteria (PGPR) possess multiple properties, particularly their ability to synthesize indole-3-acetic acid (IAA), which have been shown to enhance plant growth renders them valuable for agricultural applications. This study assessed the effects of different IAA-producing PGPR on germination and growth of rice (KDML105) under different systems to identify effective isolates. Ten PGPR with high in vitro IAA production were selected and identified based on 16S rRNA. They belonged to three genera, Klebsiella, Arthrobacter and Enterobacter and could produce IAA at 43.52 - 90.73 µg/mL in 0.01% L-tryptophan. Germination test revealed that PGPR treatment did not improve germination rate and seed vigor. Evaluation in different systems showed that treatments influenced all growth parameters when tested in nutrient solution but have no effect on root length and number when tested in soil, indicating system dependent interactions. However, greater overall growth enhancement by PGPR was observed in soil. Isolates JC1-05 (Klebsiella sp.), JO1-01 (Arthrobacter sp.), and TC2-05 (Enterobacter sp.) performed best in soil, while JC1-05 and TC2-05 also performed well in solution. Higher IAA production of these isolates indicates a partial association with growth promotion but that alone does not ensure growth enhancement, which implies that other factors contributed to the effectiveness of PGPR. Hypothetically, PGPR effectiveness could be derived from a combination of plant-microbe compatibility, optimal IAA levels and other growth-promoting properties of the bacteria. These results suggest that while IAA-producing PGPR hold promise for enhancing rice growth, their effectiveness depends on additional factors, making screening multiple isolates essential.